Supermolecular structures of recrystallized starches with amylopectin side chains modified by amylosucrase to different chain lengths. (October 2021) - Zhang, Hao; Qian, Shuo; Rao, Zhiming; Chen, Zhengxing; Zhong, Qixin; Wang, Ren
Abstract: Understanding the supermolecular structures of recrystallized starches is imperative to manufacture novel starches with controllable physicochemical properties enabling novel applications. In this study, native amylopectin (AP) from maize was modified to different chain lengths using amylosucrase from Neisseria polysaccharea . Native AP granules showed well-organized lamellar structures with a periodicity of ca. 9.0 nm whereas modified starches formed heterogeneous structures with the average crystallite size ranging from 19.77 to 29.88 nm. Acidic treatments eroded amorphous domains in both native AP granules and modified starch particles, producing nanocrystals composed of double helices. A-type nanocrystals (~40 nm) from native AP granules showed quadrangular shape with an acute angle of ca. 60°, while irregular B-type nanocrystals were observed for the modified starches. Molecular characterizations suggested that the nanocrystals had relatively uniform chain lengths (DP 16.5–25.2), and the helix length (the thickness of nanocrystals) was positively correlated to the thermal stability of starches. Graphical abstract: Image 1 Highlights: Side chains of amylopectin were elongated to different lengths. The recrystallized starches had heterogeneous structures. Long linear starch chains increased the size of crystallites. Helix length determined the thermal stability of recrystallized starches.